Discovery of sulfonamides and 9-oxo-2, 8-diazaspiro[5, 5]undecane-2-carboxamides as human kynurenine aminotransferase 2 (KAT2) inhibitors. Issue 8 (15th April 2020) - Kalliokoski, Tuomo; Rummakko, Petteri; Rantanen, Marja; Blaesse, Michael; Augustin, Martin; Ummenthala, Goverdhan Reddy; Choudhary, Sapan; Venäläinen, Jarkko
Graphical abstract: Abstract: Human kynurenine aminotransferase 2 (KAT2) inhibitors could be potentially used to treat the cognitive deficits associated with bipolar disease and schizophrenia. Although, there has been active drug research activity by several industrial and academic groups in developing KAT2 inhibitors over the years, no such compound has proceeded to the clinics. Here, we report two different chemical series of reversible KAT2 inhibitors with sub-micromolar activities. The first series was identified by a high-throughput screening of a diverse random library and the second one by structure-based virtual screening. Two novel crystal structures of KAT2 complexed with different reversible inhibitors were also deposited to the Protein databank which could be useful for future drug discovery efforts.